Severe Respiratory Distress after C Section Due to Hypertension-Related Pulmonary Edema : A Case Report - Fauzi, Achmad Ma’ruf; Kusuma, Indra (Jurnal Komplikasi Anestesi, 2024)
Introduce Pulmonary edema is a very rare complication of pregnancy. It is more commonly seen as a complication of preeclampsia. The physiopathology of this relationship is not well understood. This is a life-threatening condition that requires immediate treatment and termination of pregnancy. Case Presentation We present the case of a women 24 year old who developed preeclampsia, complicated by pulmonary edema (pe) with heart failure after elective c section under spinal anesthesia in her first pregnancy. In the Intensive Care Unit (ICU) the patient received fist using Non-invasive ventilation (niv), after six hour using niv the oxygen saturation go down, and move using ventilator intubation, using ARDS NET hight peep. Discussion Acute respiratory distress syndrome (ARDS) is a life threatening condition characterized by poor oxygenation and noncompliant or “stiff” lungs. This disorder is associated with capillary endothelial injury and diffuse alveolar damage. Many mechanisms have been proposed to explain the pathogenesis of pulmonary oedema in pre-eclampsia including hypervolaemia, left ventricular failure and pulmonary capillary leakage. Conclusion Pulmonary edema is an emergency that can occur in pregnancy with preeclasmsia which has a high mortality if not treated immediately. Early screening and adequate therapy can improve patient outcomes.